Supercapacitor Electrodes Delivering High Energy and Power Densities - Rajan, Jose; Krishnan, Syam G.; B., Vidyadharan; Izan Izwan, Misnon; M., Harilal; R. A., Aziz; J., Ismail; M. M., Yusoff (Elsevier Ltd, 2016)
Considerable progress has been achieved in developing supercapacitor materials with desirable charge storage properties; however, uniting energy density (ES) and power density (PS) in a single device is an elusive issue. We have explored diverse range of materials and structures such as (i) activated carbon from bio-resources, (ii) ceramic electrochemical materials as nanoparticles, nanowires, and nanoribbons, and (iii) layered materials to overcome this issue. An ES of ∼52.6 Wh kg-1 @ PS of ∼15000 W kg-1 is delivered using nanowire nanocomposites based device which appear to be the best ever achieved in supercapacitor charge storage mode employing aqueous alkaline electrolytes.